Assessment of carbon storage and sequestration for mitigating climate change in urban forests - Rosa Aprilia; Yuki M.A. Wardhana; Sri Setiawati Tumuyu (Applied Environmental Science, 2026)
Background: Urban forests can contribute to climate change mitigation by lowering atmospheric carbon dioxide (CO₂) concentrations, thereby enhancing ecosystem resilience in urban areas. Quantifying the carbon storage and sequestration capacities of urban forests is crucial for assessing their actual and potential roles. Interest in carbon quantification is growing; however, empirical evidence from densely populated urban forests remains limited. This study presents a case study on the quantification of carbon storage and sequestration by the Kemayoran Urban Forest, an urban forest in the city center with high population density and environmental pressure. Methods: Quantitative methods were employed to estimate carbon storage and sequestration using a non-destructive method based on allometric equations. Data collection was conducted through direct field surveys with established plot samples. Findings: This study recorded 267 tree individuals, comprising 36 species across 32 genera and 19 families. The total carbon storage was 74.83 tons C ha⁻¹, with total carbon sequestration amounting to 274.62 tons CO₂ ha⁻¹. However, this carbon assessment was limited to above-ground biomass estimates and did not include below-ground carbon stocks. Conclusion: The results indicate that the Kemayoran Urban Forest has substantial carbon storage and sequestration capacity despite being managed in an urban setting characterized by high population density and environmental pressures. Novelty/Originality of this article: This study provides empirical evidence of the carbon storage and sequestration capacity of a densely populated urban forest using a standardized non-destructive allometric approach. The findings establish baseline carbon data that support urban forest management and climate change mitigation planning.